2016
DOI: 10.1007/s00540-016-2286-y
|View full text |Cite
|
Sign up to set email alerts
|

Intrathecal morphine versus intravenous opioid administration to impact postoperative analgesia in hepato-pancreatic surgery: a randomized controlled trial

Abstract: The findings suggest that a single dose of ITM before hepatic/pancreatic surgery may offer better postoperative pain control than i.v. opioid administration during surgery. This beneficial effect is maintained throughout the first three PODs and is not associated with a higher complication rate; neither did it influence recovery parameters. ITM provides an appropriate alternative to i.v. morphine during major abdominal surgery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
34
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(39 citation statements)
references
References 19 publications
3
34
2
Order By: Relevance
“…Ten studies were included in the review (26,(29)(30)(31)(32)(33)(34)(35)(36)(37) as shown in the PRISMA diagram ( Figure 1). Six of the studies were RCTs (29-31, 33, 35, 37), two studies were retrospective observational studies (26,34), and two studies were prospective observational studies (32,36).…”
Section: Study Characteristicsmentioning
confidence: 99%
See 1 more Smart Citation
“…Ten studies were included in the review (26,(29)(30)(31)(32)(33)(34)(35)(36)(37) as shown in the PRISMA diagram ( Figure 1). Six of the studies were RCTs (29-31, 33, 35, 37), two studies were retrospective observational studies (26,34), and two studies were prospective observational studies (32,36).…”
Section: Study Characteristicsmentioning
confidence: 99%
“…Eight studies (29)(30)(31)(32)(33)(35)(36)(37) assessed postoperative analgesia as measured by pain scores. Measured against placebo, CWI and PCA, patients treated with intrathecal morphine demonstrated significantly improved pain scores for up to the first 24 hours post-operation.…”
Section: Post-operative Analgesiamentioning
confidence: 99%
“…These findings contradict previously published results. In previous studies proving the superiority of preoperative intrathecal morphine in patients undergoing hepatobiliary operations, pain severity was apparently higher both in patients with and without intrathecal morphine administration [9][10][11]. These three studies included a similar number of patients who received similar doses of the intrathecal regimen comprising 0.5 mg of morphine, 15 lg of fentanyl, 0.4 mg of morphine, and 4 lg/kg of morphine.…”
Section: Discussionmentioning
confidence: 99%
“…We used ITM as the analgesic in this study, which offers superior analgesia compared with IV opioid, IV-PCA and continuous wound infusion, for example (38). Better pain control, and subsequently reduced IV opioid consumption and PONV incidence, may facilitate ambulation, improve physical capability and prevent severe wound pain, thus resulting in a shorter hospitalization period (39,40).…”
Section: Discussionmentioning
confidence: 99%